Law Enforcement of Corruption Crimes Through the Restoration of State Finances Based on the Principles of Restorative Justice - Riyantika, Annisa (NEGREI: Academic Journal of Law and Governance, 2023)
State financial losses due to corruption arising from corruption crimes must be returned immediately. The application of the concept of restorative justice in the settlement of corruption crimes was again carried out by the Indonesian Prosecutor's Office with the issuance of SE Jampidsus Number: B765/F/Fd.1/04/2018 dated April 20, 2018 regarding Technical Guidelines for Handling Corruption Cases at the Investigation Stage, which in essence the investigation is not only limited to finding the event of Corruption in the form of unlawful acts, but also must try to find the amount of State Financial Losses. This research aims to analyze how the application of the concept of restorative justice in the law of corruption eradication in order to strengthen the goal of restoring state losses by the perpetrators of corruption crimes, which has recently increased, to find out whether the concept of restorative justice in corruption crimes can be applied in Indonesian law. The type of research used is normative legal research or library legal research, which is legal research conducted by examining library materials (library research), with a regulatory approach, concept approach and analytical approach. The results showed that the application of the concept of restorative justice in corruption crimes in order to strengthen the goal of restoring state losses by perpetrators of corruption crimes can be seen through the Circular Letter of the Deputy Attorney General for Special Crimes Number: B113/F/Fd.1/05/2010 dated May 18, 2010 and the Chief of Police Letter No. Pol. B/3022/XII/2009/sdeops on the concept of Alternative Dispute Resolution (ADR) terroristically and juridically about law enforcement and the concept of restorative justice in corruption crimes can be applied in Indonesian law